Delayed Onset and Protracted Course of Psoriasis-like Secondary Syphilitic Lesions in a HIV-seropositive Man Who has Sex with Men: A Case Report - Rui-Rui Peng; Shuxian Shang; Jia Chen; Mei Shi; Fu-Quan Long (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)